PENGARUH KEMITRAAN KOPERASI SERBA USAHA PERTIWI HIJAU TERHADAP KEBERHASILAN USAHATANI PADI ORGANIK DI KECAMATAN COLOMADU, KABUPATEN KARANGANYAR - Dwi Ayu Noviantika; Siwi Gayatri; Kadhung Prayoga (Universitas Galuh, 2022)
Problems faced by Farmers in Colomadu District is about the lack of price guarantees and market guarantees. These problems can be overcome by doing partnerships, with agriculture cooperative, for instance. Partnership is a form of cooperation between farmers and cooperative with the principle of mutual benefit. The aims of this study were (1) to describe the partnership between organic rice farmers and the Pertiwi Hijau Multipurpose Cooperative, and (2) to analyze the effect of the partnership to ward the success of organic rice farming. This research was conducted in January 2022 – February 2022, it located in Colomadu District, Karanganyar Regency. The research method used was the census method. The method of determining respondents was chosen by complete enumeration with the number of respondents of 30 farmers. Methods of data collection were done by interview and observation. The data used were primary data and secondary data. The data analysis method used was descriptive analysis and multiple linear regression analysis. The results showed that the variables of farming assistance, price guarantee, provision of production facilities and capital loans simultaneously had a significant effect toward the success of farming activity. The variables of farming assistance and credit partially had a significant effect on the success of farming activity. Based on the result, it need to revise the agreement on price guarantees and the provision of production facilities in order to improve farmer’s satisfaction.